2022
DOI: 10.1021/acs.analchem.2c00488
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mRNAs of Ribosomal Protein L15 and E-Cadherin in Living Circulating Tumor Cells at Single Cell Resolution To Study Tumor Heterogeneity

Abstract: To study the heterogeneity of circulating tumor cells (CTCs) is of crucial importance to analyze cancer progression and metastasis. However, in situ detection of highly heterogeneous CTCs in peripheral blood still faces an elusive challenge. Here, we show direct detection of two metastasis-related mRNAs of diverse CTCs in whole blood by a triple-targeting nanoprobe. In the nanoprobe, two kinds of molecular beacons, MB1 to detect RPL15 mRNA and MB2 to detect Ecadherin (E-cad) mRNA, are loaded in a highly effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…RPs are widely distributed in various tissues, and have specific transcript expression profiles in normal human tissues (Bortoluzzi et al, 2001). Recent studies showed that the expression patterns of RPs were related to various pathological conditions (Sun et al, 2022; Xu, He, et al, 2022). Multiple RPs have been found to be differentially expressed in many types of tumors, such as colorectal cancer, prostate cancer, and breast cancer (Azevedo et al, 2022; Bee et al, 2006; Markiewski et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…RPs are widely distributed in various tissues, and have specific transcript expression profiles in normal human tissues (Bortoluzzi et al, 2001). Recent studies showed that the expression patterns of RPs were related to various pathological conditions (Sun et al, 2022; Xu, He, et al, 2022). Multiple RPs have been found to be differentially expressed in many types of tumors, such as colorectal cancer, prostate cancer, and breast cancer (Azevedo et al, 2022; Bee et al, 2006; Markiewski et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As a type of oligonucleotide-based sensor recognizing specific nucleic acid sequences, MBs can realize sensitive detection of nucleic acids such as mRNAs and miRNAs. Being delivered into living cells by a delivery vector, MBs can probe intracellular RNA targets in situ at a single cell resolution. …”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Aptamers conjugated on HA are introduced to the delivery system via electrostatic interactions. The SYL3C aptamer can specifically interact with epithelial cell adhesion molecule (EpCAM) overexpressed on epithelial cancer cells, [10,22] and the CL4 aptamer can bind epidermal growth factor receptor (EGFR) overexpressed on mesenchymal cancer cells. [23] The delivery system can target all CTCs during EMT and MET processes.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, in our previous work, we developed tumor-targeting nano-systems for exerting therapeutic actions and/or probing biomarkers in CTCs. [9][10][11] As it is well known, epithelial-mesenchymal transition (EMT) and stemness are critical players in cancer progression. [12] Diverse subtyped CTCs, including CTCs in different EMT and mesenchymal-epithelial transition (MET) stages, and CTCs with varied stemness levels, may co-exist.…”
Section: Introductionmentioning
confidence: 99%